The Effectiveness of E-Learning-Based Volleyball Service Video Media on Students Affected by Covid-19 at Faculty of Sports Science, Universitas Negeri Medan - Samsuddin Siregar; Indra Kasih; Herli Pardilla (OVS LLC, 2022)
The study purpose. The online learning system, media, and resources used by lecturers to achieve volleyball learning goals are known to be not optimal. This study aimed to develop an e-learning video media that can be used by students as a learning resource to learn the material for upper serve, jump serve, and floating serve in volleyball games. Materials and methods. The research subjects were students who were divided into treatment groups and control groups where each group consisted of 40 people. The research method used was an experimental method with a before-after research design (one-group pretest and posttest design). A rubric test is an instrument used to measure the effectiveness of video media in improving student service skills. Results. The results of the research and data analysis found that the service skills (upper serve, jump serve, and floating serve) in the treatment group with the help of e-learning video media were better than in the control group who did not receive e-learning. Conclusions. The treatment group has better service skills than the control group. During the Covid-19 pandemic, it is recommended for lecturers to use e-learning video media in teaching volleyball service material.